Development of the Composition of Energy-Saving Raw Materials for Sintering Cement Clinker - Bakhriev, N. F.; Omonov, A. O. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article describes scientific research on the creation of highly efficient mineralizers based on iron dross of a rolling mill during the firing of cement clinker in order to reduce the sintering temperature. So, in modern conditions, there are acute problems of energy saving and the production of high-quality, high-strength cements, the authors propose an innovative method and scientific justification for the solution problems in the workplace. New ideas and results of experimental developments, technological regulations and practical experiments in this direction are proposed. The authors made an attempt to implement the idea by using the local iron dross of the Tashkent Metallurgical Plant as a ferrite additive during clinker firing. The joint venture Tashkent Metallurgical Plant is a super modern enterprise of New Uzbekistan, with an annual capacity of 500 thousand tons of cold-rolled steel with galvanized and polymer coating.